Colleges and schools-College of Agricultural Sciences and Technology-Industrial Technology 048
Phillip Wiechec of Sacramento (left rear), who graduated last June as an individual arts major, and Dr. Gary Grannis, associate professor of industrial arts and technology at CSUF, look on as several first grade students work on a toy airplane and sailboat last spring